ChatGPT and the AI Act - Natali Helberger; Nicholas Diakopoulos (Internet Policy Review)
It is not easy being a tech regulator these days. The European institutions are working hard towards finalising the AI Act in autumn, and then generative AI systems like ChatGPT come along! In this essay, we comment the European AI Act by arguing that its current risk-based approach is too limited for facing ChatGPT & co.